Modifying Buried Layers in Nano-MOSFET for Achieving Reliable Electrical Characteristics. (1st January 2016) - Zareiee, Meysam
Abstract : In this paper, a new nano-scale SOI MOSFET is proposed to improve the critical electrical characteristics. In the proposed modified buried layers SOI MOSFET (MB-MOSFET), three different layers are considered under the active region. A U-shape P silicon window, N + buried layer and SiO2 window under the channel region. Applying the materials with higher thermal conductivity than silicon dioxide reduces maximum temperature and controls self heating effects, significantly. Also, a new diode creates between N + source region and P silicon window that reduces the majority of the holes in the channel and causes controlled floating body effect. Also, the simulation with two dimensional ATLAS simulator shows that the mobility increases which causes higher drain current in the MB-MOSFET as it is compared to the Conventional MOSFET (C-MOSFET).